Investigating the Impact of Self-Efficacy in Learning Disaster Strategies in an On-Line Serious Game. (September 2013) - Blasko-Drabik, Holly; Blasko, Dawn G.; Lum, Heather C.; Erdem, Bilge; Ohashi, Miri
As playing serious games becomes a more viable method of teaching it is important to examine the factors that may impact successful learning. In the current study we examined whether college students could learn disaster prevention strategies from an on-line game. We measured perceptions of learning self-efficacy, enjoyment and game usability. Participants were asked to play an online serious game designed to help them learn what to do to prepare for a natural disaster (tsunami). Knowledge of disaster strategies were measured before and after two brief game periods. The results showed that players significantly improved in their knowledge and performance. The best predictor of post-test scores was the players' perceived self-efficacy at the end of the game. Players who felt that they could master the game, tended to have the highest performance scores. Enjoyment of the game also predicted performance suggesting that those who felt more positively also felt that they could master the game. In this relatively simple game space perceptions of usability were not as strong a predictor of performance.